Penggunaan Metode Diskusi Untuk Meningkatkan Hasil Belajar Fikih Pada Siswa Kelas 6 Mi Bahrul Ulum Turirejo Kedamean Gresik - Muslihatin Asiyah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Education and learning are separate entities. Learning is a form of the implementation of education. Learning is the process of interaction of learners with educators and learning resources in a learning environment. The learning environment is a formal education that is a place to help students in developing themselves so that the sons of the nation are born who in their souls have embedded a blend of values between intellectual, ethical and personality of the nation. The type of research conducted is Classroom Action Research. How the use of discussion methods can improve the learning outcomes of halal and haram beverage material fiqh in the 6th-grade students of MI Bahrul Ulum Turirejo Kedamean Gresik. The result of research in this study is that the learning process will be more creative because all students can express their opinions, students will be more active and not feel bored. So that by using the discussion method the learning process will be more fun, active, creative and not boring so that by using discussion methods, students' learning outcomes can improve.